LANGUAGE SHORTCOMINGS OF CURRENT LEGISLATION - Akerke Amanovna, Мединаева (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article discusses the shortcomings identified by comparing the version of the current legislation of the Russian and Kazakh languages.